2021
DOI: 10.1149/1945-7111/ac2101
|View full text |Cite
|
Sign up to set email alerts
|

Self-Ordering of Porous Anodic Alumina Fabricated by Anodizing in Chromic Acid at High Temperature

Abstract: Anodizing Al in chromic acid is a very useful surface finishing process for corrosion protection and nanoscale porous structure fabrication, whereas the self-ordering of porous anodic alumina (PAA) in chromic acid has never been found to date. Herein, we provide a self-ordered PAA film possessing numerous sub100-nm-scale characteristic bumps through anodizing in chromic acid at high temperature. Anodizing of high purity Al plates in a 0.3 M chromic acid solution at conventional low temperatures, such as 293 K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The pore arrangement of APA obtained under normal anodization conditions is disordered, with large variations in pore size and pore shape; however, APA with an ordered arrangement of uniformly sized pores can be obtained under appropriate anodization conditions. [15][16][17] This is because the pore size uniformity of APA increases with pore arrangement regularity. 18 In addition, the texturing of Al using a mold with an ordered arrangement of protrusions can also produce ordered APA consisting of pores with a remarkably high uniformity with a relative standard deviation of less than 4%.…”
mentioning
confidence: 99%
“…The pore arrangement of APA obtained under normal anodization conditions is disordered, with large variations in pore size and pore shape; however, APA with an ordered arrangement of uniformly sized pores can be obtained under appropriate anodization conditions. [15][16][17] This is because the pore size uniformity of APA increases with pore arrangement regularity. 18 In addition, the texturing of Al using a mold with an ordered arrangement of protrusions can also produce ordered APA consisting of pores with a remarkably high uniformity with a relative standard deviation of less than 4%.…”
mentioning
confidence: 99%
“…The anodization times for the first anodization were (a) 30 min and (b) 14 h. For comparison, Figure c shows the SEM image and histogram of ideally ordered anodic porous alumina prepared by the texturing process. In the histograms, the higher the proportion of pores with six neighboring pores, the closer the pore arrangement is to a hexagonally close-packed arrangement, meaning that the pore arrangement is more regular . The histograms in Figure a–c show that the percentages of pores with six neighboring pores were (a) 45, (b) 70, and (c) 100%, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…79 Quite good pore ordering with the interpore distance of ca. 340 nm was also obtained in 0.3 M chromic acid solution at 120 V and relatively high temperature of 348 K. 80 It was observed that the PAA film grown in the initial stage possessed the highest regularity which decreased with anodizing time due to pore branching during anodizing. Additionally, elemental analysis revealed that the chromate anions were not incorporated within any PAA film; thus, the ordered PAA film consisted of pure anodic aluminum oxide.…”
Section: Experimental Strategiesmentioning
confidence: 86%
“…What's more, it was suggested that the anion constituents may play a key role in the redistribution of the electric field within the barrier layer and accordingly in determining the local stress, film plasticity, and flow rate, affecting thus cell symmetry and pore dimensions. To support this assumption the examples of PAA formed in borax 139 and chromic acid 80 electrolytes was invoked that were free of incorporated electrolyte species and were characterized by a less regular morphology. Similar behavior of a tungsten tracer in the porous alumina was observed during anodization of aluminum layer in sulphuric, 140 malonic, and oxalic acid 141 solutions.…”
Section: A Pinch Of Theory On the Paa Growthmentioning
confidence: 99%